2006
DOI: 10.1158/0008-5472.can-06-1448
|View full text |Cite
|
Sign up to set email alerts
|

17β-Hydroxysteroid Dehydrogenase 14 Affects Estradiol Levels in Breast Cancer Cells and Is a Prognostic Marker in Estrogen Receptor–Positive Breast Cancer

Abstract: Estrogens have an important role in the progression of breast cancer. The 17B-hydroxysteroid dehydrogenase (17HSD) family has been identified to be of significance in hormonedependent tissues. 17HSD1 and 17HSD2 are the main 17HSD enzymes involved in breast cancer investigated this far, but it is possible that other hormone-regulating enzymes have a similar role. 17HSD5 and 17HSD12 are associated with sex steroid metabolism, and 17HSD14 is a newly discovered enzyme that may be involved in the estrogen balance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 17 publications
2
56
0
Order By: Relevance
“…Most studies on the 17βHSDs have primarily assessed type 1 and type 2 as the mediators of intratumoral interconversion of E 1 and E 2 and have focused on associations with clinical outcome rather than intratumoral estrogen levels (9,41). HSD17B12 has been suggested to be a more important source of intratumoral E 2 than either HSD17B1 or HSD17B7 due to its higher expression levels in the breast (23).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the 17βHSDs have primarily assessed type 1 and type 2 as the mediators of intratumoral interconversion of E 1 and E 2 and have focused on associations with clinical outcome rather than intratumoral estrogen levels (9,41). HSD17B12 has been suggested to be a more important source of intratumoral E 2 than either HSD17B1 or HSD17B7 due to its higher expression levels in the breast (23).…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen 17b-HSDs have been identified to date (Jansson et al 2006, Lukacik et al 2006, Luu-The et al 2008, all requiring NAD(P)(H) for activity (Shi & Lin 2004). All but one, 17b-HSD type 5 (17b-HSD5), an aldo-keto reductase (Penning et al 2000), are short-chain dehydrogenases/ reductases (Peltoketo et al 1999, Duax et al 2005, Vihko et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of cDNA from total RNA was performed using the 1 st strand cDNA Synthesis kit with random hexameres (Roche Diagnostics Corporation, Indianapolis, IN, USA). mRNA expression of 17βHSD1 and 17βHSD2 was analysed according to Gunnarsson et al [11] and 17βHSD5 according to Jansson et al [13]. β-actin was used as endogenous reference gene and the assay was purchased from Applied Biosystems (Warrington, UK).…”
Section: Semi-quanitative Real Time-pcrmentioning
confidence: 99%
“…17βHSD5 converts androstendione to testosterone and oestrone to oestradiol. We have previously shown that 17βHSD1, 17βHSD2, 17βHSD5 and 17βHSD14 are important as prognostic and treatment predictive factors in breast cancer [10][11][12][13]. It has been shown that progestins influence the oestradiol and testosterone levels, and these effects have been presumed to be an effect caused by altered regulation of 17βHSD enzymes; however the contribution of separate family members of the 17βHSD-family has not been addressed [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%